If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -15x + -6 = 40 Reorder the terms: -6 + 8x + -15x = 40 Combine like terms: 8x + -15x = -7x -6 + -7x = 40 Solving -6 + -7x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7x = 40 + 6 Combine like terms: -6 + 6 = 0 0 + -7x = 40 + 6 -7x = 40 + 6 Combine like terms: 40 + 6 = 46 -7x = 46 Divide each side by '-7'. x = -6.571428571 Simplifying x = -6.571428571
| 7.5r+2=-284 | | 7(5x-10)=4(4x-8) | | 8-1(3x+4)=6x | | 20+3z=-4 | | -.6=-.3u | | 3x^2+0x-42=0 | | x^2=2-x | | px-p^2+5x+25=0 | | (8x+7)(7x+8)=0 | | 4Z=4.8 | | (3x-4)(8x+2)=0 | | 7a+4b-3a-b= | | 8+5n=-2 | | -3W=24 | | 9x=2x+44 | | 0.02+7=0.03x+5 | | Y=4(22-4)3(6)+6 | | 3(5x+2)-7(x+1)=71 | | 0.87500000x=0.77777778 | | 97-2541-23=k | | 8=0.66666666667x | | 37-918-11=d | | -0.6x=-24 | | 9=5m-2 | | 5x-5=x | | 88x-14=88x-15 | | 33+4y-5=14y-12-2y | | 4n-3=7n+6 | | 0.2z=-30 | | 4/5x+3/5=3 | | 10.25n=24 | | 3x^2-2y^2+2x-3y+5=0 |